MANAJEMEN KOMUNIKASI RADIO START FM DALAM MEMPERTAHANKAN PENDENGAR DI DAERAH PANYABUNGAN KOTA MANDAILING NATAL - Rizka Fadillah; Ernita Arif; Sarmiati Sarmiati (Ensiklopedia of Journal, 2022)
Radio Start FM as one of the media that develops and competes with local radios in Panyabungan City of Mandailing Natal in maintaining and increasing audiences/listeners. So it takes the ability or strategy and expertise to retain old listeners and attract new radio listeners as well as analyze the communication strategies used in retaining listeners and advertising promotions. Regulations in the broadcasting sector that bring about various changes provide new challenges for broadcast media managers. Radio as a broadcasting industry requires creativity and expertise to win the competition. The purpose of this study was to analyze the communication strategy of Start FM radio in retaining listeners in the Panyabungan Mandailing Natal area. Analyzing the communication strategy of Start FM radio in the promotion of Panyabungan area advertisements in Mandailing Natal City. This study used qualitative research methods. The results of this study resulted in how the communication strategy of Radio Start FM in retaining listeners and advertising promotion in the Panyabungan area, Mandailing Natal Regency.